Technological Challenges and Opportunities in Telemedicine: Advancements and Barriers in the Pandemic Era - Samsidar; Muhammad Atnang; Syaiful Bachri Mustamin; Sahriani (Science Tech Group, 2024)
This study analyzes various aspects and challenges of telemedicine technology implementation based on findings from 10 related journals. The evolution of telemedicine has transformed healthcare services, becoming more efficient, especially during the COVID-19 pandemic. Telemedicine is applied in areas such as remote consultations, telemonitoring, teletherapy, and telepharmacy, with emerging technologies like AI, VR, and blockchain showing great potential for further enhancement. Key factors influencing the acceptance of telemedicine by healthcare professionals include perceived usefulness, attitude, compatibility, and ease of use. While telemedicine offers significant benefits, challenges such as privacy issues, regulatory barriers, and accessibility remain. Ethical and legal concerns, including the quality of care, data security, and continuity of services, are also highlighted as major issues. This study recommends understanding end-user needs and establishing better standards for future telemedicine implementation.